NON-HYDROCARBON GASES USAGE CAPABILITY ASSESSMENT FOR METHANE DESORPTION ENHANCEMENT DURING NATURAL GAS FIELDS DEVELOPMENT WITH LOW PERMEABLE RESERVOIRS - Гедзик, Назарій Миколайович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article presents the results of theoretical and laboratory research of the possibility of using non-hydrocarbon gases for enhance methane desorption from the surface of rocks during the development of natural gas fields with low permeable reservoirs. After statistical analysis of the experimental results mathematical model that combines the number of adsorbed gas, pressure, temperature and reservoir permeability was obtained. Relative adsorption capacity of tight sands for methane, nitrogen and carbon dioxide were determined experimentally. Directions for further research was grounded and the correct conclusions was made.